Pengagihan zakat kepada sektor pendidikan di Perak: Kajian di Majlis Agama Islam dan Adat Melayu Perak / Khairul Azhar Abdul Aziz - Khairul Azhar , Abdul Aziz (2017)
Educational funding is one of the most important forms of fundings to the poor and needy recipients because education is one of the most important methods that can change the lives of these people and issue of poverty. There are a few of the less fortunate financially to pursue such as the poor and needy recipients who only rely on obligatory education for school fees paid and receive aid. The aim of this study was to identify schemes and forms of educational assistance given by the Majlis Agama Islam Perak (MAIAMPk) to the recipients in their studies at the school level or at the level of higher education as well as re-evaluate educational support schemes and methods of determining the limit kifayah to the recipients in the field of education. This study used a qualitative research methodology, namely by collecting data through library research and field research using interview methods. While the method of data analysis using inductive methods. This study used a sample of the data collection and distribution of zakat made by MAIAMPk and formulate the success of the distribution of zakat in the education sector. The results showed that the obligatory education plays a very important role for the recipients to help eradicate poverty and long-term challenges faced by institutions in distributing zakat obligatory education the recipients. The study also suggests a number of approaches that can be taken to meet the challenges of today as one of the efforts by MAIAMPk to ensure the obligatory role of education in line with the objectives achieved pensyariatan alms to Muslims in the future.